2021
DOI: 10.3390/ijerph18052697
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Multidisciplinary Professional Teams during Assessment Processes for ATD Selection in the Japanese Public Provision System

Abstract: Selection of assistive technology devices (ATDs), which are imperative for persons with disabilities to improve their quality of life, requires collaboration of users and multidisciplinary professionals. However, it is still unknown how to design and implement an adequate collaborative work flow and a professional team. Under Japanese governmental ATD provision system, based on the application by clients, ATDs are mainly selected through collaborative processes with the clients and health professionals in publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The local municipalities are responsible for the direct health and rehabilitation of the end-user, whilst at the regional level, AT centres provide common resources and expertise (Sund, 2017). The clear articulation of responsibilities and focus on providing expert knowledge and reliable information builds a foundation for good practices and efficient resource management (Suzurikawa, et al 2021). The decentralised approach of the framework delivers a user-centred solution that tailors AT provisions for individual needs.…”
Section: Nordic Modelmentioning
confidence: 99%
“…The local municipalities are responsible for the direct health and rehabilitation of the end-user, whilst at the regional level, AT centres provide common resources and expertise (Sund, 2017). The clear articulation of responsibilities and focus on providing expert knowledge and reliable information builds a foundation for good practices and efficient resource management (Suzurikawa, et al 2021). The decentralised approach of the framework delivers a user-centred solution that tailors AT provisions for individual needs.…”
Section: Nordic Modelmentioning
confidence: 99%
“…Despite this ease with which usage can begin, the standard users of MMSs have often suffered considerable decline in their sensory and cognitive functions, in addition to movement functions [16,17]. While PWCs are usually prescribed by medical professionals based on a careful assessment of the individual's body functions [18], MMSs are likely to be acquired personally without any consultations with professionals [19,20]. Interview-based studies of MMS users showed that these users have concerns over safety issues, and the quality and quantity of the training that they each received on acquisition of an MMS differed greatly between individuals [21,22].…”
Section: Introductionmentioning
confidence: 99%